General phase regularized reconstruction using phase cycling - Ong, Frank; Cheng, Joseph Y.; Lustig, Michael (Magnetic resonance in medicine, 2018)
Purpose To develop a general phase regularized image reconstruction method, with applications to partial Fourier imaging, water–fat imaging and flow imaging. Theory and Methods The problem of enforcing phase constraints in reconstruction was studied under a regularized inverse problem framework. A general phase regularized reconstruction algorithm was proposed to enable various joint reconstruction of partial Fourier imaging, water–fat imaging and flow imaging, along with parallel imaging (PI) and compressed sensing (CS). Since phase regularized reconstruction is inherently non‐convex and sensitive to phase wraps in the initial solution, a reconstruction technique, named phase cycling, was proposed to render the overall algorithm invariant to phase wraps. The proposed method was applied to retrospectively under‐sampled in vivo datasets and compared with state of the art reconstruction methods. Results Phase cycling reconstructions showed reduction of artifacts compared to reconstructions without phase cycling and achieved similar performances as state of the art results in partial Fourier, water–fat and divergence‐free regularized flow reconstruction. Joint reconstruction of partial Fourier + water–fat imaging + PI + CS, and partial Fourier + divergence‐free regularized flow imaging + PI + CS were demonstrated. Conclusion The proposed phase cycling reconstruction provides an alternative way to perform phase regularized reconstruction, without the need to perform phase unwrapping. It is robust to the choice of initial solutions and encourages the joint reconstruction of phase imaging applications. Magn Reson Med 80:112–125, 2018. © 2017 International Society for Magnetic Resonance in Medicine.